Cutting out the middleman : a case study of blockchain-induced reconfigurations in the Swiss financial services industry - Witzig, Pascal (My University, 2018)
Blockchain-technology promises to have far-reaching economic and social implications, which are not yet foreseeable in its extent. It threatens to disintermediate many wellestablished sectors of the economy, and incumbent businesses might be overtaken by ambitious newcomers. The financial services industry is particularly “ripe for disintermediation” since blockchain-technology has with Bitcoin and other cryptocurrencies its first real-world use case. Incumbent businesses have to react if they do not wish to perish. However, technological evolution also affects the State and other governmental bodies: institutional frameworks or territorial arrangements can become obsolete or detrimental to business activity and may need to be amended. This paper aimed to examine ongoing technology-induced reconfigurations in the financial services industry through a four lenses framework. The technology, actors and their discourses, as well as the regulatory environment and affected territories, need to be considered all at once. We have applied this framework to the case of Switzerland: a country with an influential financial services industry that has seen better days. We have found that (1) the Swiss Confederation has swiftly adapted its institutional framework to the new reality in order to foster competition and innovation; (2) there are some raucous controversies between challengers and incumbent businesses. However, a tacit compromise allows them to coexist; (3) four “crypto-clusters” are emerging. These are located in traditional banking centers (Zurich, Zug, Lake Geneva region, Chiasso) that are seeking to strengthen their international visibility and improve their competitiveness.
Keywords: Blockchain; Bitcoin; Cryptocurrencies; Financial Services Industry; Innovation; Technology; Creative Destruction; Economies of Worth